Mixture effects of oxygenated PAHs and benzo[a]pyrene on cardiovascular development and function in zebrafish embryos. (October 2020) - Cunha, Virgínia; Vogs, Carolina; Le Bihanic, Florane; Dreij, Kristian
Highlights: Some oxygenated PAHs induce higher levels of cardiovascular toxicity in zebrafish embryos than PAHs. Exposure to binary mixtures generally caused enhanced toxicity. Cardiovascular toxicity was associated with deregulation of several cardiac-specific genes. Cardiovascular toxicity was dependent of aryl hydrocarbon receptor. Abstract: Polycyclic aromatic compounds (PACs), including polycyclic aromatic hydrocarbons (PAHs) and oxygenated PAHs (oxy-PAHs), are common environmental pollutants known to cause health effects in humans and wild-life. In particular, vertebrate cardiovascular development and function are sensitive to PACs. However, the interactive effects of PAHs and oxy-PAHs on cardiovascular endpoints have not been well studied. In this study, we used zebrafish embryos (ZFEs) as a model to examine developmental and cardiovascular toxicities induced by the three environmental oxy-PAHs benzo[ a ]fluorenone (BFLO), 4 H -cyclopenta[ def ]phenanthren-4-one (4H-CPO) and, 6 H -benzo[ cd ]pyren-6-one (6H-BPO), and the PAH benzo[ a ]pyrene (BaP) either as single exposures or binary oxy-PAH + PAH mixtures. 6H-BPO induced developmental and cardiovascular toxicity, including reduced heartbeat rate and blood flow, at lower doses compared to the other compounds. Exposure to binary mixtures generally caused enhanced toxicity and induction of aryl hydrocarbon receptor (AhR)-regulated gene expression ( ahr2 and cyp1a ) compared to single compound exposure. This was associated with differential expression of genes involved in cardiovascular development and function including atp2a2, myh6, tbx5 and zerg . AhR-knock-down significantly reduced the cardiovascular toxicity of 6H-BPO and its binary mixture with BaP indicating a significant AhR-dependence of the effects. Measurements of internal concentrations showed that the toxicokinetics of BaP and 6H-BPO were altered in the binary mixture compared to the single compound exposure, and most likely due to CYP1 inhibition by 6H-BPO. Altogether, these data support that similar to interactions between PAHs, mixtures of PAHs and oxy-PAHs may cause increased developmental and cardiovascular toxicity in ZFEs through an AhR-dependent mechanism.